Peer influence on primary school children’s social judgment-making: an experimental study - Nicolay, Philipp; Hank, Corinna; Egger, Sara; Müller, Christoph M.; Huber, Christian (Frontiers in Education, 2025)
IntroductionPeer influence is often studied with regard to the development of specific behaviors (e.g., maladaptive behavior, prosocial behavior) in adolescents. Following a broader understanding of peer influence, this study investigated if children at primary school age are also influenced by peers when making social judgments about other students and to what degree social anxiety is associated with greater susceptibility to peer influence.MethodsA total of 103 (Mage = 9.18 years) primary school children participated in a computer-based experiment. Participants made social judgments regarding 22 pictures of potential exchange students in three consecutive trials (T1, T2, T3). For T1 and T2, general variability in participants’ ratings was assessed without experimental manipulation. For T3 (manipulation), participants were introduced to social-judgments allegedly made by peers that contradicted their earlier ratings. They were then asked to rate the 22 pictures again.ResultsRandom-Intercept linear mixed models were used to analyze the data. Findings indicate that participants’ social judgments aligned significantly more with manipulated peer ratings than in the absence of manipulation. This shift toward the peer ratings was higher when peers’ social judgments were more negative than participants’ ratings compared to cases where peers made more positive social judgments than participants. Social anxiety did not predict how much participants’ social judgments shifted toward those made by peers. However, a significant interaction between social anxiety and the direction of the manipulation (positive vs. negative) was found. Greater social anxiety was associated with a stronger effect of peer influence toward more positive social judgments.DiscussionFindings suggest that peer influence as a process is relevant in the primary school context and in regard to everyday decision-making as to whom individual children want to interact with. While this effect was particularly pronounced for peer influence toward more negative social judgments, social anxiety moderated this effect. Implications for research and practice are discussed.